PPARγ Plays an Important Role in Acute Hepatic Ischemia-Reperfusion Injury via AMPK/mTOR Pathway - Liwei Wu; Qiang Yu; Ping Cheng; Chuanyong Guo (PPAR Research, 2021)
Background. Hepatic ischemia-reperfusion (IR) injury is one of the severe complications associated with liver surgery and leads to liver dysfunction. PPARγ is always linked with various physiologic pathways, and it can alleviate liver damage in IR injury. Aim. In this study, we explored the potential mechanism of PPARγ in the pathogenesis of hepatic IR injury by mice model. Methods. After treated with si-PPARγ or rosiglitazone, mice were subjected to hepatic ischemia-reperfusion. Liver tissue and blood samples were collected to evaluate liver injury and detected relative mRNA and protein expressions. Results. The expression of PPARγ was increased after reperfusion. And the alleviation of PPARγ aggravated the liver damage in IR; at the same time, upregulation of the expression of PPARγ released the liver damage. And these effects of PPARγ in IR were related to the AMPK/mTOR/autophagy signaling pathway. Conclusion. PPARγ plays an important role in hepatic IR injury at least partly via the AMPK/mTOR/autophagy pathway.